Respuesta :
[tex]f(g(x))=1/x^2+9/x\Rightarrow f(g(-1))=-8[/tex]
[tex]f(g(x))=1/(x^2+9x) \Rightarrow g(f(1/2))=4/19[/tex]
[tex]f(g(x))=1/(x^2+9x) \Rightarrow g(f(1/2))=4/19[/tex]
Answer:
-8
2/19
Step-by-step explanation:
We must substitute x=-1 into g(x) and then the answer of g(x) we must substiute as x into f(x). Similarly we must substitute x=1/2 into f(x) and the answer as x into g(x):
1. x=-1 into g(x)
[tex]=1/-1=-1[/tex]
substitute x=-1 into f(x)
[tex]=(-1)^2+9\cdot(-1)=-8[/tex]
2. x=1/2 into f(x)
[tex]=(1/2)^2+9\cdot(1/2)=19/2[/tex]
substitute x=19/2 into g(x)
[tex]=1/(11/2)=2/19[/tex]